Experimental study and a physical model on the geomorphic response mechanisms of meandering rivers under progressive sediment reduction - Zhao, Zhanchao; Yao, Shiming; Jiang, Enhui; Qu, Bo (Frontiers in Earth Science, 2022)
Abstract: Influenced by human activities, including high dam construction, soil and water conservation, and sand mining in the upper reaches of rivers, the amount of sediment entering the lower reaches of the river decrease significantly. The human activities disturb the natural balance between river evolution and water as well as sediment movement and induce new characteristics of the river evolution. After the construction and operation of the Danjiangkou Reservoir and the Three Gorges Reservoir of the Yangtze River (China) different degrees of bend bypassing and shoal cutting in the bends downstream of the dams are observed. The reason for this interrelation has not been explained sufficiently. Based on the analysis of prototype observation data and physical model experiment, we have investigated the evolution mechanism of different topographic types of meandering rivers under the condition of decreasing sediment inflow. The data generated by our model experiment document that the sediment concentration of the convex bank flow with large degree of curvature of the bend is lower than that of the concave bank flow for a reduction of the sediment concentration from 100% to 0%. Moreover, the convex bank of the bend gradually collapses and retreats, whereas the main channel of the river gradually swings, with a swing range is 0-800m, towards the convex bank. This phenomenon becomes more significant with progressive reduction of the sediment inflow. Combined with theoretical analysis, we interpret that the drastic reduction of the amount of sand that has destroyed the relative natural balance of sediment transport in the riverbanks and river channels in the meandering river section is the main reason for the occurrence of bypassing and shoal cutting in the meandering river section of plain alluvial rivers especially during the mid- to high-water period, the capacity of sediment transport in the mainstream belt exceeds the sediment concentration in the water body significantly and is coupled with the change of the runoff process caused by the regulation of the reservoir operation. As a consequence, the river beach is constantly scouring and developing. The evolution is generally characterized by bend bypassing and shoal cutting.